PENGEMBANGAN E-LKPD MENGGUNAKAN LIVEWORKSHEET BERBASIS RADEC BERBANTUAN MIND MAP PADA SISTEM PERNAPASAN MANUSIA DI KELAS V SEKOLAH DASAR - Indah Kartika; Risda Amini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of utilization and use of technology in accordance with the times and the less varied appearance of LKPD causes the appearance of LKPD that is less attractive so that students are less motivated, less creative, less initiative to express opinions, and less collaborative in working on LKPD. Therefore, this research was carried out with the aim of developing E-LKPD using RADEC-based Liveworksheets assisted by Mind Map . This research is a Research and Development (R&D) research using a 4D model. With the Define (define), Design (design, Develop, and Disseminate (spread) stages. Data from this study was obtained from the results of validation, and practicality. The validation sheet is filled out by material, language and media experts. Meanwhile, the practicality sheet is filled in by teachers and students. Then the trial was carried out in class V, namely SDN 02 Lubuk Alung by 28 students and at SDN 15 Lubuk Alung by 28 students. The results of this study produced LKPD in the form of E-LKPD using RADEC-based Liveworksheets assisted by Mind Map that are valid and practical. The overall validation results obtained a percentage of 94.77% with the category "Very Valid". The practical results of the questionnaire of the average response of teachers and students from the 2 test schools can be found that learning using E-LKPD using RADEC-based Liveworksheets assisted by Mind Map is "very practical" with an average of 96.27% and 95.71%. Meanwhile, the percentage of responses from teachers and students at the research school of SDN 17 Lubuk Alung by 24 students to E-LKPD using RADEC-based Liveworksheets assisted by Mind Map with an average of 96.27% and 95.13%. Thus, the use of E-LKPD using RADEC-based Livewoksheets assisted by Mind Map on the human respiratory system in grade V of elementary school was declared valid and practical.